Establishing A Greenhouse For Melon Cultivation: A Community Service Program To A Farmer Group In Lamongan Jawa Timur - Pratono, Aluisius Hery; Budiarto, Bambang; Djuwari, Djuwari; Djumadi, Firman Rosjadi; Setyaningrum, Idfi; Rajamin, Irza Meingindra Putri; Sundari, Made Siti; Ariani, Mintarti; Hariadi, Sugeng; Solekha, Rofiatun (Universitas AMIKOM Yogyakarta, 2023)
The demand for fresh and high-quality melon has been steadily growing over the years. Certainly, supply chain challenges significantly impact farmers' ability to produce and distribute their products efficiently for some reasons. Moreover, melon crops are vulnerable to changes in weather and climate. Support in the form of climate-resilient farming practices, weather forecasting, and access to drought-resistant or heat-tolerant varieties can help farmers mitigate risks. Hence, melon farmers, like farmers of any other crop, require support for various reasons due challenging industry, and farmers often face a range of factors that can impact their performance. This article aims to explore how a community service program support a farmer group in Lamongan Jawa Timur by establishing a greenhouse for melon cultivation. The primary focus of a community development report is to document the planning, implementation, progress, and outcomes of a specific community development program. Data collection for a community development report involves qualitative approaches such as surveys, interviews, focus groups, and observations. The method follows the sequential step: The initial step is gathering information about the community's needs, challenges, and aspirations by conducting online interviews, and offline focus group discussion to understand the specific areas that require improvement. The second step is stakeholder mapping, which includes community members, local leaders, local university partners, and local business partners who have a vested interest in the program. The third step entails assessing potential risks and challenges that could hinder the development process. This includes identifying economic, social, environmental, or cultural risks. Based on the information gathered in the previous steps, the design of the community development program was to set clear goals, objectives, strategies, and action plans by tailoring to address the specific needs and circumstances of the community. Last, putting the program into action involves executing the strategies and action plans outlined in the program design, which includes organizing workshops, training sessions, and infrastructure development. The results show that community development is a dynamic and iterative process. Flexibility and adaptability are key qualities as the situation on the ground may change, and new insights may emerge. Additionally, involving the community at every stage of the process fosters ownership, empowerment, and sustainability of the development initiatives.